Non-high-density lipoprotein cholesterol vs low-density lipoprotein cholesterol as a risk factor for ischemic stroke: a result from the Kailuan study. (1st June 2013) - Wu, Jianwei; Chen, Shengyun; Liu, Liping; Gao, Xiang; Zhou, Yong; Wang, Chunxue; Zhang, Qian; Wang, Anxin; Hussain, Mohammed; Sun, Baoying; Wu, Shouling; Zhao, Xingquan
<x xml:space="preserve">Abstract</x> Objectives: To compare the predictive value of serum low-density lipoprotein (LDL) cholesterol and non-high-density lipoprotein (non-HDL) cholesterol levels for ischemic stroke in the Chinese population. Methods: We performed a four-year cohort study of 95 778 men and women, aged 18-98 years, selected from the Kailuan study (2006-2007). Baseline LDL cholesterol levels were estimated using direct test method. Total cholesterol levels were estimated using endpoint test method. The predictive values of LDL cholesterol and non-HDL cholesterol for ischemic stroke were compared. Results: During the follow-up period, there were 1153 incident cases of ischemic stroke. The hazard ratio (HR) for ischemic stroke in the top quintile of LDL cholesterol was the highest among five quintiles (HR: 1·25; 95% confidence interval (CI), 1·01-1·53). The HR in the top quintile of non-HDL cholesterol for ischemic stroke was also the highest among five quintiles (HR: 1·53; 95% CI, 1·24-1·88). Analysis of trends showed a significant positive relationship between ischemic stroke incidence and serum LDL cholesterol level, and non-HDL cholesterol level, respectively (both P < 0·05). The area under the curve of LDL cholesterol and non-HDL cholesterol for ischemic stroke was 0·51 and 0·56, respectively (P < 0·05 for the difference). Conclusions: Serum Non-HDL cholesterol level is a stronger predictor for the risk of ischemic stroke than serum LDL cholesterol level in the Chinese population.